Utilizing student-generated games to enhance procedural knowledge and attitude toward learning in physics - Guce, John Mikko M. (College of Education, University of the Philippines Diliman, 2017)
This study investigated the utilization of student-generated physics games learning technique in enhancing procedural knowledge and attitude toward learning in physics of Grade 9 students. The effect of procedural knowledge on predicting attitude toward learning in physics was also analyzed. Lastly, the effect of attitude toward learning in physics in procedural knowledge was also studied.